Implementation of Consumer Rights in the Digital Trading Ecosystem: A Qualitative Study of Marketplace and Social Media Users: JEL Classification: D18, K24, L81, L86, M31 - Samsul Bahri; Nursahdi Saleh; Sucianti Sukianna Sari (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The rapid growth of digital commerce in Indonesia has increased the use of marketplaces and social media as major transaction platforms. However, alongside these developments, various issues related to consumer rights protection continue to emerge. This study aims to analyze the implementation of consumer rights within the digital commerce ecosystem, focusing on users of marketplaces and social media. The research employed a descriptive qualitative approach using in-depth interviews, observation, and documentation techniques. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of consumer rights in digital commerce has not been fully optimized. Most consumers understand their basic rights but lack comprehensive knowledge regarding consumer protection regulations, personal data protection, and dispute resolution mechanisms. Marketplaces generally provide better consumer protection through complaint handling systems, refund features, and seller rating mechanisms, while transactions conducted through social media tend to pose higher risks due to limited supervision and the absence of standardized protection mechanisms. The major challenges identified include low consumer awareness of their rights, product-information discrepancies, online fraud risks, slow complaint responses, and inadequate monitoring of social commerce activities. The study concludes that effective consumer protection in digital commerce requires collaboration among government institutions, digital platform providers, business actors, and consumers through improved digital literacy, stronger regulatory enforcement, and enhanced transaction security systems.